First two bilateral hand transplantations in India (Part 3): Rehabilitation and immediate outcome - Sharma, Mohit; Iyer, Subramania; Kishore, P.; Mathew, Jimmy; Vijayaraghavan, Sundeep; Sankaran, Ravi; Nair, Arun N.; Janarthanan, R.; Wakure, Abhijeet; Reddy, Raghuveer; Chetan Mali, S. M.; Varma, Visakh; Chaudhari, Ashish; Dhake, Swapnil; Omkumar, Akshay (Indian Journal of Plastic Surgery, 2017)
Introduction: This report covers the strategies adopted for rehabilitation for the first and second dual hand transplants performed in India. Materials and Methods: The team, under a trained physiatrist, including physiotherapy and occupational therapy personnel, was involved in the management of both these patients. The management protocol was developed considering previous reports as well as our management strategies in the rehabilitation of the replanted hands. The involvement of the team with the patients started in the 1st week itself and continued on a daily basis for the entire year. Results: Outcome analysis was performed at 6 months and 1 year using the disability of shoulder and hand evaluation and hand transplant scoring system. Functional magnetic resonance imaging was done at the end of 1 year to assess the cortical integration of the transplanted hand. Conclusion: Despite more than 110 hands being transplanted worldwide, hand transplant remains an experimental procedure. It is still not considered the “standard of care” for hand amputees. Outcome analyses performed worldwide do indicate that the procedure can provide a substantial improvement in the quality of life for the hand amputee, especially the bilateral amputees.
Keywords: Composite tissue allotransplantation; disability of shoulder and hand; hand transplant scoring system; rehabilitation after hand transplantation; vascularised composite allotransplantation